Results, meta-analysis and a first evaluation of UNOxR, the urinary nitrate-to-nitrite molar ratio, as a measure of nitrite reabsorption in experimental and clinical settings - Tsikas, Dimitrios; Hanff, Erik; Bollenbach, Alexander; Kruger, Ruan; Pham, Vu Vi; Chobanyan-Jürgens, Kristine; Wedekind, Dirk; Arndt, Tanja; Jörns, Anne; Berbée, Jimmy F. P.; Princen, Hans M. G.; Lücke, Thomas; et al. (Amino acids, 2018)
We recently found that renal carbonic anhydrase (CA) is involved in the reabsorption of inorganic nitrite (NO 2 − ), an abundant reservoir of nitric oxide (NO) in tissues and cells. Impaired NO synthesis in the endothelium and decreased NO bioavailability in the circulation are considered major contributors to the development and progression of renal and cardiovascular diseases in different conditions including diabetes. Isolated human and bovine erythrocytic CAII and CAIV can convert nitrite to nitrous acid (HONO) and its anhydride N 2 O 3 which, in the presence of thiols (RSH), are further converted to S -nitrosothiols (RSNO) and NO. Thus, CA may be responsible both for the homeostasis of nitrite and for its bioactivation to RSNO/NO. We hypothesized that enhanced excretion of nitrite in the urine may contribute to NO-related dysfunctions in the renal and cardiovascular systems, and proposed the urinary nitrate-to-nitrite molar ratio, i.e., U NOx R, as a measure of renal CA-dependent excretion of nitrite. Based on results from clinical and experimental animal studies, here, we report on a first evaluation of U NOx R. We determined U NOx R values in preterm neonates, healthy children, and adults, in children suffering from type 1 diabetes mellitus (T1DM) or Duchenne muscular dystrophy (DMD), in elderly subjects suffering from chronic rheumatic diseases, type 2 diabetes mellitus (T2DM), coronary artery disease (CAD), or peripheral arterial occlusive disease (PAOD). We also determined U NOx R values in healthy young men who ingested isosorbide dinitrate (ISDN), pentaerythrityl tetranitrate (PETN), or inorganic nitrate. In addition, we tested the utility of U NOx R in two animal models, i.e., the LEW.1AR1- iddm rat, an animal model of human T1DM, and the APOE*3 - Leiden.CETP mice, a model of human dyslipidemia. Mean U NOx R values were lower in adult patients with rheumatic diseases (187) and in T2DM patients of the DALI study (74) as compared to healthy elderly adults (660) and healthy young men (1500). The intra- and inter-variabilities of U NOx R were of the order of 50% in young and elderly healthy subjects. U NOx R values were lower in black compared to white boys (314 vs. 483, P = 0.007), which is in line with reported lower NO bioavailability in black ethnicity. Mean U NOx R values were lower in DMD (424) compared to healthy (730) children, but they were higher in T1DM children (1192). ISDN (3 × 30 mg) decreased stronger U NOx R compared to PETN (3 × 80 mg) after 1 day ( P = 0.046) and after 5 days ( P = 0.0016) of oral administration of therapeutically equivalent doses. In healthy young men who ingested NaNO 3 (0.1 mmol/kg/d), U NOx R was higher than in those who ingested the same dose of NaCl (1709 vs. 369). In LEW.1AR1- iddm rats, mean U NOx R values were lower than in healthy rats (198 vs. 308) and comparable to those in APOE*3 - Leiden.CETP mice (151).